<h3>
Answer: A. 18*sqrt(3)</h3>
=============================================
Explanation:
We'll need the tangent rule
tan(angle) = opposite/adjacent
tan(R) = TH/HR
tan(30) = TH/54
sqrt(3)/3 = TH/54 ... use the unit circle
54*sqrt(3)/3 = TH .... multiply both sides by 54
(54/3)*sqrt(3) = TH
18*sqrt(3) = TH
TH = 18*sqrt(3) which points to <u>choice A</u> as the final answer
----------------------
An alternative method:
Triangle THR is a 30-60-90 triangle.
Let x be the measure of side TH. This side is opposite the smallest angle R = 30, so we consider this the short leg.
The hypotenuse is twice as long as x, so TR = 2x. This only applies to 30-60-90 triangles.
Now use the pythagorean theorem
a^2 + b^2 = c^2
(TH)^2 + (HR)^2 = (TR)^2
(x)^2 + (54)^2 = (2x)^2
x^2 + 2916 = 4x^2
2916 = 4x^2 - x^2
3x^2 = 2916
x^2 = 2916/3
x^2 = 972
x = sqrt(972)
x = sqrt(324*3)
x = sqrt(324)*sqrt(3)
x = 18*sqrt(3) which is the length of TH.
A slightly similar idea is to use the fact that if y is the long leg and x is the short leg, then y = x*sqrt(3). Plug in y = 54 and isolate x and you should get x = 18*sqrt(3). Again, this trick only works for 30-60-90 triangles.
Wouldn’t the faces be the triangle parts ? Like p,q,o p,m,q n,o,q
Okay so your equation is going to be : 18= 5k + 3.25p
Answer:
I believe the answer will be 30 queen bee books.
[ Answer ]

[ Explanation ]
4(y + 6) - 2(y - 2)
[Expand] 4(y + 6): 4y + 24
4y + 24 - 2(y - 2)
[Expand] -2(y - 2): -2y + 4
4y + 24 - 2y + 4
[Simplify] 4y + 24 - 2y + 4: 2y + 28
= 2y + 28
![\boxed{[ \ Eclipsed \ ]}](https://tex.z-dn.net/?f=%5Cboxed%7B%5B%20%5C%20Eclipsed%20%5C%20%5D%7D)